(untitled) (Eduscotech, 2022)
Special Education Teacher Training (PLB) for children with autism in East Java represents a strategic effort to improve the quality of education for children with Autism Spectrum Disorder (ASD). This program aims to introduce and implement learning methods that are responsive to the specific needs of children with autism, as well as to equip special education teachers with the knowledge and skills required to manage effective and inclusive classrooms. Through this training, teachers are expected to gain a deeper understanding of the characteristics of children with autism, enhance their competencies in designing adaptive curricula, and apply appropriate instructional techniques to support students’ social, cognitive, and emotional development. The training program also emphasizes the importance of collaboration among teachers, parents, and the wider community in creating an inclusive and supportive learning environment for children with autism. By strengthening professional capacity and collaborative practices, this initiative seeks to foster more responsive and adaptive educational services. The results of this training are expected to contribute positively to the improvement of educational quality for children with special needs in East Java, particularly children with autism, by promoting inclusive practices and enhancing teachers’ readiness to address diverse learning needs effectively.